IMF Staff Papers, Volume 50, No. 1 - Flood, Robert (IMF Staff Papers; IMF Staff Papers ;, 2003)
Forty years ago, Marcus Fleming and Robert Mundell developed independent models of macroeconomic policy in open economies. Why do we link the two, and why do we call the result the Mundell-Fleming, rather than Fieming-Mundell model?